Label-free detection of conformational changes in switchable DNA nanostructures with microwave microfluidics - Angela C. Stelson (Nature Portfolio, 2019)
Methods to study conformational changes in biomolecules are limited in resolution and require labelling or other modifications of target analytes. Here the authors present a label-free, microwave microfluidic approach to detect conformational changes of DNA nanostructures based on ionic conductivity.